2006
DOI: 10.1534/genetics.105.053389
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Drosophila Uncoupling Protein 5 in Metabolism and Aging

Abstract: A novel uncoupling protein, UCP5, has recently been characterized as a functional mitochondrial uncoupler in Drosophila. Here we demonstrate that UCP5 knockout (UCP5KO) flies are highly sensitive to starvation stress, a phenotype that can be reversed by ectopic neuronal expression of UCP5. UCP5KO flies live longer than controls on low-calorie diets, have a decreased level of fertility, and gain less weight than controls on high-calorie diets. However, isolated mitochondria from UCP5KO flies display the same re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 34 publications
0
43
0
Order By: Relevance
“…They had a lower body composition of sugars (glucose and trehalose), and during starvation, their triglyceride reserves were used up faster compared to controls. These data indicate that DmUCP5 is important for maintaining metabolic homeostasis in the fly and might influence the hormonal control of metabolism (Sanchez-Blanco et al 2006).…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…They had a lower body composition of sugars (glucose and trehalose), and during starvation, their triglyceride reserves were used up faster compared to controls. These data indicate that DmUCP5 is important for maintaining metabolic homeostasis in the fly and might influence the hormonal control of metabolism (Sanchez-Blanco et al 2006).…”
Section: Introductionmentioning
confidence: 79%
“…Previous studies have indicated the presence of two UCP isoforms in insects, UCP4 and/or UCP5 (Jezek 2002; Sanchez-Blanco et al 2006). Therefore, polyclonal antibodies raised against human UCP4 and rat UCP5 were used in total mitochondrial proteins to evaluate the presence of UCP in fat body and muscle from the cockroach G. coquereliana.…”
Section: Immunological Detection Of G Cocquereliana Ucp (Gcucp)mentioning
confidence: 99%
See 2 more Smart Citations
“…and the effects of CR, sirtuins and resveratrol on mitochondrial function (Haigis et al ., 2006;Lagouge et al ., 2006;Lopez-Lluch et al ., 2006;Nemoto et al ., 2006;Sanchez-Blanco et al ., 2006). Given the intense activity in the field, there should be many more illuminating discoveries just over the horizon.…”
mentioning
confidence: 99%